Comparative Study of Water Rights Trade Price in Various Countrieswith Different Systems: A Case Study of Zhanjiang City - YE Changxin; SU Chunsheng; FANG Chunyan; CHEN Xiaohong (Renmin Zhujiang)
Water rights trade is an important way for countries from all over the world to usemarket mechanisms to optimize water resource allocation and solve water problems. Taking ZhanjiangCity as an example, this paper studies the differences in the price of water rights between twodifferent countries——China and the United States by the method of full-cost pricing, analyzesthe adaptability of water rights trade on these two countries in terms of the pricing mechanism ofwater rights trade, and construction, supervision and management mechanism of water rights trademarket, and finally puts forward some suggestions for promoting the further development of waterrights trade in China.